Comparative study of breast cancer with or without concomitant Paget disease: An analysis of the SEER database. (28th May 2019) - Chen, Shijing; Chen, Huaquan; Yi, Ying; Jiang, Xuemei; Lei, Hai; Luo, Xue; Chen, Yu; Liu, Sha; Yuan, Dan; Jia, Xinjian; Li, Junyan
Abstract: Background: Most mammary Paget disease (MPD) is associated with underlying in situ or invasive breast cancer. The objective of this study was to compare the clinicopathological characteristics and survival outcomes between breast cancer with Paget disease (PD) and breast cancer alone. Methods: From the Surveillance, Epidemiology, and End Results (SEER) database, 2000‐2015, of the US National Cancer Institute, we identified 1569 women who had PD with invasive ductal carcinoma (PD‐IDC) and 1489 women who had PD with ductal carcinoma in situ (PD‐DCIS). Independent demographic and clinicopathological variables as well as survival outcomes of these patients were compared to patients with the corresponding breast cancer without concomitant PD. Results: PD‐IDC and PD‐DCIS both had worse survival outcomes and poorer tumor characteristics than the corresponding disease without PD. Contrary to in the breast cancer alone groups, in the breast cancer with PD groups, the HR status ( P  = 0.182 in PD‐IDC and P  = 0.371 in PD‐DCIS), HER2 status ( P  = 0.788 in PD‐IDC and P  = 0.643 in PD‐DCIS), and combined molecular subtype ( P  = 0.196 in PD‐IDC and P  = 0.853 in PD‐DCIS) were not found to affect disease prognosis. After matching tumor characteristics and treatment approaches, PD‐IDC as well as PD‐DCIS exhibited no significant difference in disease prognosis with corresponding IDC and DCIS. Finally, by comparative analysis, a kind of PD‐DCIS (ICD‐O‐3 code 8543/3) showed many invasive behaviors (31.8% of 8543/3 patients had stage I‐III cancer) and was associated with worse survival outcomes than the other type of PD‐DCIS. Conclusions: Breast cancer with concomitant PD was associated with more aggressive tumor characteristics and worse survival outcomes. The HR status, HER2 status, and combined molecular subtype could not affect the prognosis of breast cancer with PD. Moreover, a portion of the PD‐DCIS cases were invasive breast cancer cases that required special treatment. Abstract : Our study indicated that breast cancer with PD had more aggressive tumor characteristics and worse survival outcomes. The HR status, HER2 status, and combined molecular subtype could not affect the prognosis of breast cancer with PD. Moreover, a portion of the PD‐DCIS cases were invasive breast cancer cases that required special treatment